2021
DOI: 10.1186/s43020-021-00041-3
|View full text |Cite
|
Sign up to set email alerts
|

Indoor navigation: state of the art and future trends

Abstract: This paper reviews the state of the art and future trends of indoor Positioning, Localization, and Navigation (PLAN). It covers the requirements, the main players, sensors, and techniques for indoor PLAN. Other than the navigation sensors such as Inertial Navigation System (INS) and Global Navigation Satellite System (GNSS), the environmental-perception sensors such as High-Definition map (HD map), Light Detection and Ranging (LiDAR), camera, the fifth generation of mobile network communication technology (5G)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(44 citation statements)
references
References 81 publications
0
28
0
1
Order By: Relevance
“…A summary of some of the essential works is presented in Tables 2 and 3. Based on all this knowledge and also after reviewing a few more works [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], it was found that there has not been more research work that focused on detecting an invalid predicted location based on the speed of the pedestrians in an indoor environment. So, a model that depends on Recurrent Neural Network and uses the speed of pedestrian navigation to adjust the predicted location label is proposed, which is discussed in Sect.…”
Section: Related Workmentioning
confidence: 99%
“…A summary of some of the essential works is presented in Tables 2 and 3. Based on all this knowledge and also after reviewing a few more works [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], it was found that there has not been more research work that focused on detecting an invalid predicted location based on the speed of the pedestrians in an indoor environment. So, a model that depends on Recurrent Neural Network and uses the speed of pedestrian navigation to adjust the predicted location label is proposed, which is discussed in Sect.…”
Section: Related Workmentioning
confidence: 99%
“…Sementara jika dilihat berdasarkan Citation Bursts terdapat 10 besar berdasarkan kata kunci. Berdasarkan gambar 6, ditinjau siapa penelitinya, Sisi Zlatanova mendominasi dengan 23 penelitian dengan beberapa penelitiannya seperti [10], [11] dan [12] diikuti oleh El-Sheimy dengan 13 penelitian dengan penelitian terbarunya yaitu [13] serta Asakawa dengan 10 Penelitian.…”
Section: Gambar 2 Cluster Pada Penelitian DI Bidang Navigasi Dalam Ruanganunclassified
“…To resolve these issues, many studies successfully employed other onboard sensors to provide alternative solutions to the positioning problem in GPS-denied environments [5]. The most commonly used onboard sensors include ultrasonic rangers, laser rangers, light detecting and ranging (Lidar) sensors, and visual cameras [6].…”
Section: Introductionmentioning
confidence: 99%